1990
DOI: 10.1111/j.1365-2621.1990.tb01073.x
|View full text |Cite
|
Sign up to set email alerts
|

Partial characterization of the in situ activity of pectinesterase in Bramley apple

Abstract: The characteristics of pectinesterase (PE) have been examined in waste material (peel, cores and offcuts) obtained from Bramley seedling apples barn stored for 2 , 4 and 12 weeks. A crude enzyme extract was prepared by suspending the dried and milled apple waste in 0.1 M NaCl at pH 8.5. The activity of PE under standard assay conditions of 0.5% apple pectin, 0.1 M NaCl, pH 8.5 and 30°C was low, between 4 and 8 units g-' dry matter, but activities up to 60 units g-' dry matter were obtained at higher temperatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
2
2
0
1
Order By: Relevance
“…The E a value obtained for C. pubescens PME was 36.27 kJ/mol. This result was in agreement with the E a values reported for tomato PME (34.32-38.10 kJ/mol) (Nakagawa et al, 1970) and PME in crude protein extracts isolated from Bramley apple waste (39.2 kJ/mol) (King, 1990(King, , 1991. However, it was higher than E a values (23-31 kJ/mol) reported for most plant PMEs (Table 2) (Lee & Wiley, 1970;Rexova´-Benkova´& Markovic, 1976;Fayyaz, Asbi, Ghazali, & Che Man, 1995;Denes et al, 2000).…”
Section: Effect Of Temperature On Pme Activitysupporting
confidence: 94%
See 1 more Smart Citation
“…The E a value obtained for C. pubescens PME was 36.27 kJ/mol. This result was in agreement with the E a values reported for tomato PME (34.32-38.10 kJ/mol) (Nakagawa et al, 1970) and PME in crude protein extracts isolated from Bramley apple waste (39.2 kJ/mol) (King, 1990(King, , 1991. However, it was higher than E a values (23-31 kJ/mol) reported for most plant PMEs (Table 2) (Lee & Wiley, 1970;Rexova´-Benkova´& Markovic, 1976;Fayyaz, Asbi, Ghazali, & Che Man, 1995;Denes et al, 2000).…”
Section: Effect Of Temperature On Pme Activitysupporting
confidence: 94%
“…Excess of metal ions, however, might be related with the decrease in activity by inhibition of PME, because they might be bonded to carboxylate groups, neighboring the ester bonds that are required for the reaction of PME (Lineweaver & Ballou, 1945). The NaCl concentration found for the maximum activity of C. pubescens PME (0.4 moles/L NaCl) was close to the value of 0.33 moles/L NaCl reported for carrot PME (Alonso, Canet, Howell, & Alique, 2003), but was higher than that of the general range (0.025-0.2 moles/L) reported for other plant PME's (Hills & Mottern, 1945;King, 1990;Laurenco & Catutani, 1984;Nakagawa, Yanagawa, & Takehana, 1970;Rexova´-Benkova´& Markovic, 1976). This suggested that C. pubescens PME exhibited tolerance to Na + ions.…”
Section: 32supporting
confidence: 76%
“…Electrostatic repulsion provided by the negative charges present in the partly demethylated pectin by galacturonic acid residues (Beveridge, 1999b) also contributed to the stability of suspensions of hydrated cloud particles. However, if methoxy content of pectic compounds dropped below a critical level because of the action of pectin methylesterase (PME) in apples, the system is not stable (Castaldo et al, 1989;King, 1990;Genovese et al, 1997). The low methoxy pectic compounds form insoluble pectates with divalent ions, such as Ca 2þ and cause the growth of particles (Javeri and Wicker, 1991;Baker and Cameron, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…La enzima pectinmetilesterasa (EC. 3.1.1.11; PME) está relacionada con la degradación de las sustancias pécticas de la laminilla media de la célula, componente de la pared celular que actúa como agente cementante o ligando entre las células y puede también controlar los movimientos de materiales solubles (Proctor y Miesle, 1991;King, 1990). Aziz y Yusof (1994) reportaron actividad de la enzima PME en frutos de guanábana.…”
Section: Enzymatic Activityunclassified
“…The enzyme pectinmethylesterase (EC 3.1.1.11; PME) is related to the degradation of the pectic substances of the cell's middle lamella, a component of the cell wall that acts as a cementing agent or ligand between cells and can also control movements of soluble materials (King, 1990;Proctor and Miesle, 1991). Aziz and Yusof (1994) reported activity of the PME enzyme in soursop fruits.…”
Section: Enzymatic Activitymentioning
confidence: 99%